If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11x+4=8x+10
We move all terms to the left:
11x+4-(8x+10)=0
We get rid of parentheses
11x-8x-10+4=0
We add all the numbers together, and all the variables
3x-6=0
We move all terms containing x to the left, all other terms to the right
3x=6
x=6/3
x=2
| 54=u+8u | | -12=-x/3-9 | | -6(q-83)=-90 | | 1/2a=2/3a-8 | | 7(z+80)=-56 | | 9w+w=8 | | -3+7x+42=10x+15 | | 8+9j–=2j | | -16t^2+60t=10t | | (13+2/5)+(-2/5(10+1/5))=w | | 4=x+44 | | 6=-47.52-v | | t=12+3/4 | | 4x-1+91=12x-6 | | 4,096=32(p+40) | | 5=m5+8 | | 11+9c=47 | | 51=4t | | -4=k3-7 | | c/19=17 | | 12v+3v+v+2v-8v=10 | | x2-6=2 | | n-104=-1 | | 20s-19s+4s=20 | | F(x)=210(1.08^x) | | z−(−12)=15 | | F(x)=210(1.08^) | | p+310=-1 | | h-57/8=3 | | 2y−y=13 | | c+3c+3c-4c-2c=19 | | -8(4x+8)=9 |